Evaluasi Pembelajaran Pendidikan Agama Islam Di Sma Negeri 3 Bengkalis - Silvi Ismayanti; Afrianti Alyana; Maria Ulfa; Siti Khairiah (Universitas Pakuan, 2026)
EVALUATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING AT STATE SENIOR HIGH SCHOOL 3 BENGKALIS Learning evaluation plays a crucial role in determining the success of students' learning process. The purpose of this study is to describe the implementation of Islamic Religious Education learning evaluation on self-control material at SMA Negeri 3 Bengkalis. The study used a descriptive qualitative approach with data collection through observation, interviews, and documentation. The data were then processed using the Miles and Huberman analysis stages. The results show that the assessment of the cognitive aspect was carried out through written tests, the affective aspect by observing student attitudes, and the psychomotor aspect by observing students' skills in applying self-control during learning. Although the implementation has gone quite well, several obstacles still exist, such as differences in student abilities, limited time in assessing attitudes, and difficulties monitoring student behavior outside the classroom. To overcome these obstacles, teachers provide guidance, positive behavioral habits, and ongoing mentoring.